The thermal damaging process of diorite under microwave irradiation (Fracture and Structural Integrity, 2018)
Laboratory tests have been conducted to investigate the effects of thermal damage on diorite under microwave irradiation. The sample rocks were heated to high temperature range of 300 to 800 ℃ in a single-mode microwave furnace. The experimental results show that the rocks started to crack at 500 ℃ and completely disintegrated at 700 ℃. The intensities of quartz diffraction peaks were almost unchanged while the diffraction peak intensity of hornblende gradually decreased with temperature increasing. In addition, the chlorite diffraction peak disappeared at 500 ℃. The compressive strength of the sample decreased to 40% at 600 ℃ and it approached zero at 700 ℃. In this paper, the possible reasons for the thermal effects on the fracture of diorite were discussed, which can be related to water evaporation, thermal cracks and mismatch thermal expansion, and phase transition on quartz. The result indicates that diorite can be effectively destroyed under microwave irradiation.
Keywords: Microwave heating; Thermal damage; Diorite; Rock breakage